The Agrarian Paradox: An Impact of Foreign Labour Migration and Remittances on Agricultural Activities in Mahottari, Nepal - Thapaliya, Krishna Prasad; Acharya, Kiran; Chaudhary, Sunil; Nepali, Rajan; Poudel, Sangita (Journal of Agriculture and Forestry University, 2026)
Foreign labour migration has emerged as a significant socioeconomic phenomenon in Nepal, contributing substantially to the national economy through remittance inflows while also causing labour shortage and serious challenges for the sustainability and productivity of the agricultural sector. This study investigates the effects of foreign labour migration and remittances on agricultural activities in Bardibas Municipality. Using a mixed-methods approach, data were collected from migrant household heads and key informants. For quantitative data, respondents were selected using simple random sampling, whereas qualitative respondents were selected purposively. Quantitative data were analyzed in SPSS, and qualitative data were transcribed, thematically categorized, interpreted, and integrated with the quantitative findings. In 2024, the study found that labour migration is driven by both unemployment and sociopsychological motivations, such as the pursuit of social prestige, and that 88% of migrants prefer to migrate to GCC (Gulf Cooperation Council) nations. Although 88.3% of migrant households send remittances home through formal banking channels, these remittances have contributed to the “Lost Labour Effect.” Consequently, the agricultural sector is experiencing women’s empowerment through the “Feminization of Agriculture and Workload Pressure.” Female workload pressure refers to the increased labour burden on women, particularly in preparing inputs. On the positive side, remittance receipts have enabled the adoption of hybrid seeds (90.6%) and irrigation systems (93.8%) by overcoming liquidity constraints. More than three-fourths of returned migrants were engaged in subsistence farming, suggesting a limited reintegration effect. Overall, the findings indicate that remittances primarily function as a form of economic security or insurance for households. However, these remittances have yet to contribute to structural transformation through capital formation in the agricultural sector, thereby ensuring enhanced growth and development in rural Nepal.